The Impact of Genetic Polymorphisms in Glutamate-Cysteine Ligase, a Key Enzyme of Glutathione Biosynthesis, on Ischemic Stroke Risk and Brain Infarct Size - Polonikov, Alexey; Bocharova, Iuliia; Azarova, Iuliia; Klyosova, Elena; Bykanova, Marina; Bushueva, Olga; Polonikova, Anna; Churnosov, Mikhail; Solodilova, Maria (Life (Basel, Switzerland), 2022)
The purpose of this pilot study was to explore whether polymorphisms in genes encoding the catalytic (GCLC) and modifier (GCLM) subunits of glutamate-cysteine ligase, a rate-limiting enzyme in glutathione synthesis, play a role in the development of ischemic stroke (IS) and the extent of brain damage. A total of 1288 unrelated Russians, including 600 IS patients and 688 age- and sex-matched healthy subjects, were enrolled for the study. Nine common single nucleotide polymorphisms (SNPs) of the GCLC and GCLM genes were genotyped using the MassArray-4 system. SNP rs2301022 of GCLM was strongly associated with a decreased risk of ischemic stroke regardless of sex and age (OR = 0.39, 95%CI 0.24–0.62, p < 0.0001). Two common haplotypes of GCLM possessed protective effects against ischemic stroke risk (p < 0.01), but exclusively in nonsmoker patients. Infarct size was increased by polymorphisms rs636933 and rs761142 of GCLC. The mbmdr method enabled identifying epistatic interactions of GCLC and GCLM gene polymorphisms with known IS susceptibility genes that, along with environmental risk factors, jointly contribute to the disease risk and brain infarct size. Understanding the impact of genes and environmental factors on glutathione metabolism will allow the development of effective strategies for the treatment of ischemic stroke and disease prevention.